Prediksi Pemilihan Jurusan Siswa Kelas 1 SMK Menggunakan Jaringan Syaraf Tiruan dengan Metode Backpropagation - Mhd. Furqan; Yusuf Ramadhan Nasution; Rabiatul Adawiyah Hasibuan (STMIK Budi Darma, 2021)
Student learning potential can be seen or meansured in various ways, one of them by concluding it’s success in learning. The value of subjects is one indicator that isused as a references to conclude studentlearning success academically. Artificial Neural Networks have the ability to learn and produce rules or operations from some input examples that are entered and make predictions. Backpropagation isone method that is often used in solving complex problems because the network with this method is trained using guided learning methods.